CONCEPTIONS OF SELF/NO-SELF AND MODES OF CONNECTION Comparative Soteriological Structures in Classical Chinese Thought - Berkson, Mark A. (Journal of religious ethics, 2005)
This essay examines the ways that the terms “self” and “no-self” can illuminate the views of classical Chinese thinkers, particularly Confucians such as Confucius, Mencius, and Xunzi, and the Daoist thinker Zhuangzi. In particular, the use of the term “no-self ” to describe Zhuangzi's position is defended. The concepts of self and no-self are analyzed in relation to other terms within the thinkers' “concept clusters”—specifically temporality, nature, and social roles—and suggestions are given for constructing typologies that sort out the range of meanings of self and no-self based on the characteristics of the relations among terms within the concept clusters. The essay focuses on the way that the Confucians and Zhuangzi use concepts of self and no-self, respectively, as soteriological strategies that aim at making connections with larger systems or wholes, and it concludes that different connections are emphasized by the Confucians and Zhuangzi precisely because the various connections are made possible and sustained by different conceptions of self, temporality, nature, and social roles.